“DIA SMART” Android-Based Intelligent Application Expert System for Diagnosis and Mapping of 10 Diseases at Teaching Factory Nutrition Care Center - Selviyanti, Erna; Roziqin , Mochammad Choirur; Putra, Dony Setiawan Hendyca; Noor , Muhammad Syeikhoni (International Journal of Health and Information System, 2023)
The Basic Health Research in 2018 showed that the prevalence of non-communicable diseases including cancer, stroke, chronic kidney disease, diabetes mellitus, and hypertension increased in Indonesia. The main risk factors are metabolic factors, behavioral factors, and environmental factors. Based on the existing problems, an Android-based intelligent application for the diagnosis and mapping of 10 diseases was proposed at the Teaching Factory Nutrition Care Center. This application development used the Expert System Development Life Cycle model and Dart Language. The framework used is Flutter. This article only discusses the implementation and testing of applications made based on Android. This application was developed to perform a diagnosis based on some patients’ data. This application is used as a reference for early detection of a disease, allowing patients to take preventive measures. It can map the number of patients who had health consultations in each department. The users of the application were a doctor, nutritionist or health consultant at the Teaching Factory Nutrition Care Center. System functionality tested using Blackbox-testing showed that the application ran well.